If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(2 + x) = -12 (2 * -4 + x * -4) = -12 (-8 + -4x) = -12 Solving -8 + -4x = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -4x = -12 + 8 Combine like terms: -8 + 8 = 0 0 + -4x = -12 + 8 -4x = -12 + 8 Combine like terms: -12 + 8 = -4 -4x = -4 Divide each side by '-4'. x = 1 Simplifying x = 1
| -4-(-2)/-4= | | (5-3i)(8+i)=0 | | 420/15 | | 7x-(2x+1)=7-(x-4) | | 7s=21s-350 | | -18+16= | | 3*x+1=40 | | 3+1/2x=-4 | | 12/5w=13/10 | | r/-5-3=-14 | | -y^2+3y=9y+9 | | -3(2x+8)+6x= | | B-a/x | | 7y+9=Yt-6 | | h-18= | | -7(w-4)+3w-27=0 | | 16v^2+17v-45=0 | | 3w+4-w=5w+7-m | | 5m+4=4m | | -5(w-9)+8w+2= | | 2x^2-16x+29=0 | | -4x-7=-43 | | -6x-2=x-23 | | 5.3x+2=12.7-2 | | 7x/10=5 | | 3x-2/7=5/6 | | 6x-40=45 | | -6(4p+3)-49=5(2p+7) | | 4x^2=-24-20x | | 4.2x+31.5=-65.1 | | -86=4+10x | | 3.9x-13=1.7x+31 |